Análise da viabilidade técnica e econômica do pavimento de transição, considerando concreto armado, protendido e alvenaria estrutural - Ramos, Filipe Gimenez (2019)
The choice of the structural building system depends on the analysis and evaluation of the designer, which is based on some parameters to make his decision, such as the type of building, its use and also the costs arising from this choice. Another important factor today is the environmental impact, so it is becoming increasingly important to study new construction techniques such as the use of structural masonry. To try to meet these demands and make possible greater use of structural masonry, this work compares two widespread structural systems, reinforced concrete, and prestressed concrete, for a transition floor to support a building, built-in structural masonry, with the variation of 8 and 12 floors. From the survey of loads and horizontal actions, transition floors were dimensioned within the limit states ELU and ELS, comparing the quantitative of materials, changing the reinforced concrete and prestressed concrete systems, as well as the gaps between pillars. Thus, prestressed concrete systems proved to be more advantageous in terms of material quantities and approximate average cost, with systems with a reduced span between columns being the most economical in terms of materials use and the most cost-effective 12 story buildings more viable concerning the cost per transition area.